Determinants of Factors Influenced the Follow-up of BPK RI Audit Recommendations - Artha, Sandrin; Dewata, Evada; Nurhasanah, Nurhasanah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the Factors That Affected the Follow-Up of BPK Audit Recommendations on Provincial Government in Indonesia. The research data uses secondary data obtained from the overview of the BPK examination results on provincial local governments in Indonesia. The object of this research is 34 provinces in Indonesia with a research period of fiscal year 2018-2022 so the number of samples is 170. Hypothesis testing using panel data regression analysis with the help of Econometric Views version 12: Audit findings and the number of Regional Apparatus Organizations have a joint (simultaneous) effect on the follow-up of BPK audit results.